John Thelwall in the Wordsworth Circle - Thompson, J. author. aut Link
XVI, 313 p.
Keywords: In this book, Judith Thompson restores a powerful but long-suppressed voice to our understanding of British Romanticism. Drawing on newly discovered archives, this book offers the first full-length study of the poetry of John Thelwallas well as his partnership with Samuel Taylor Coleridge and William Wordsworth.